Comparative genomic analysis of Parageobacillus thermoglucosidasius strains with distinct hydrogenogenic capacities - Teresa Mohr; Habibu Aliyu; Raphael Küchlin; Michaela Zwick; Don Cowan; Anke Neumann; Pieter de Maayer (BMC Genomics, 2018)
Abstract Background The facultatively anaerobic thermophile Parageobacillus thermoglucosidasius produces hydrogen gas (H2) by coupling CO oxidation to proton reduction in the water-gas shift (WGS) reaction via a carbon monoxide dehydrogenase–hydrogenase enzyme complex. Although little is known about the hydrogenogenic capacities of different strains of this species, these organisms offer a potentially viable process for the synthesis of this alternative energy source. Results The WGS-catalyzed H2 production capacities of four distinct P. thermoglucosidasius strains were determined by cultivation and gas analysis. Three strains (DSM 2542T, DSM 2543 and DSM 6285) were hydrogenogenic, while the fourth strain (DSM 21625) was not. Furthermore, in one strain (DSM 6285) H2 production commenced earlier in the cultivation than the other hydrogenogenic strains. Comparative genomic analysis of the four strains identified extensive differences in the protein complement encoded on the genomes, some of which are postulated to contribute to the different hydrogenogenic capacities of the strains. Furthermore, polymorphisms and deletions in the CODH-NiFe hydrogenase loci may also contribute towards this variable phenotype. Conclusions Disparities in the hydrogenogenic capacities of different P. thermoglucosidasius strains were identified, which may be correlated to variability in their global proteomes and genetic differences in their CODH-NiFe hydrogenase loci. The data from this study may contribute towards an improved understanding of WGS-catalysed hydrogenogenesis by P. thermoglucosidasius.